The Teaching - Learning Process Of English At Mts Terpadu Al Mustaqim 2012/2013 A Micro Ethnographic Study - Prabowo, Sindhung; , Prof. Dr. Endang Fauziati, M. Hum; , Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
The objectives of the study is to reveal briefly of teaching learning process at MTs Terpadu Al Mustaqim in which encompases syllabus, learning objective, instructional material, teaching design, evaluation and strength-weaknesses.The research was conducted ethnographic study. The learning objectives are general and specific learning outcome.The instructional material devided into printed, audio and visual material. Teacher'role are controller, observer, organizer, and explainer. The student's role are processor, performer, listener. The classroom procedure are three pattern namely: BKOF-MOT-JCOT-ICOT, BKOF-MOTJCOT, BKOF-MOT-JCOT. The classroom activities are advance organizer, presentation, classroom practice, role play, comprehension, answer question and reading aloud. The media are grouped into two forms. The first is printed media such as picture, rainbow envelop and colourful letter. The second is unprinted media entails slide, cassete and compact disk. The evaluation describes evaluation model and kind of evaluation. The evaluation model are dialogue completation task, multiple choice and cloze procedural text. The kind of evaluation involves formative and summative evaluation. There are strength and weakness among the instructional design of English teaching at MTs Terpadu Al Mustaqim.Rely on the finding, discussion, conclusion and implication, the writer suggest for English teacher to encourage students' engagement in the classroom. The application of diverse method, technique is obviously need in English teaching. He also recommended for future researcher to expand the study in other research field.